Clinical profile of recent progressive illnesses in patients with mucormycosis: a comprehensive analysis - Sharma, Shrikant; Singhal, Mukul; Bhandari, Sudhir (International Journal of Research in Medical Sciences, 2022)
Background: The COVID-19 pandemic, in its omnipresence, descended an unprecedented blow on the reeling facilities nationwide, which at its stabilising junction posed another threat – mucormycosis. Potentially immunodeficient cases, diabetes and excessive rampancy of steroids propagated this neo-epidemic, currently challenging the fretting mortality rate. Aim of the study was to analyse the clinical profile elaborating the recent illnesses and progression in patients admitted with mucormycosis in a dedicated ‘mucor-care’ centre. Methods: Total 195 admitted patients were evaluated based on their COVID protocol management and oxygen therapy administered with special emphasis on hygiene maintenance in view of mask support, oral care and hospitalisation course with duration and medications provided. Type and duration of glucocorticoids, injectable or oral, dispensed to the patients were duly logged and analysed. Results: Half cases (50%) were found COVID reverse transcriptase-polymerase chain reaction (RT-PCR) positive with 69% patients suffering from moderate ailment and above. Patients averaged 25-30 days at onset of post-COVID mucormycosis symptomatology with 78% (172) cases having h/o hospitalisation. 90% patients required oxygen therapy in variable magnitudes with meagre 38% receiving ‘remdesivir’ complete course dosages. Despite being prudent, 58% did not maintain adequate sanitation while 72% denied having oxygen humidified. Steroids were pivotal with 84% affirmative prevalence; dexamethasone being commonest, averaging 15 days of therapy, which supplementing immune-compromised modalities, promulgated this epidemic. Conclusions: The deadly trinity of diabetes, rampancy of steroids in a background of COVID-19 caused havoc in recent times. Only astute usage of resources and prudent education can curb this menace in a better way.